ANALISIS PELAKSANAAN KEWENANGAN BADAN PERMUSYAWARATAN DESA (BPD) DI DESA BERUMBUNG BARU KECAMATAN DAYUN KABUPATEN SIAK - Nur Sidhik Ariswanto; Syafril Abdullah (UIR Press, 2018)
The body of the Consultative village (BPD) is the embodiment of democratic institutions in the Organization of the Government of the village. BPD can be considered as Parliament's village. BPD is a new institution in the village in the autonomous region in Indonesia after the enactment of law No. 32 of 2004 Concerning regional Governments and Government Regulation No. 72 in 2005 About the village. With the BPD is expected to shut down various what the weaknesses and shortcomings of the Government that its implementation should not be out of the corridor empowerment and smart village community. The purpose of this research is: to know the implementation Authority in Berumbung Baru Village BPD Subdistrict Dayun, Siak Regency and to know the obstacles affecting the implementation of the Authority's Berumbung Baru Village BPD Subdistrict Dayun Siak Regency. The indicators in this study are discussed the Draft Regulations of the village Along the village head; carry out Surveillance Against the rules and regulations of the Village the village head; Propose the appointment and dismissal of the head of the village; to form the Election Committee Head village; digging, Accommodate, Gather, Formulate, and Channeling the aspirations of Communities; compile the code of conduct. The type of research that be located in this Office Berumbung Baru village is a research survey that is descriptive. The respondents in this study was the head of the village chief, Dayun, Secretary of the village, BPD, RW, and RT. as for technique the withdrawal of samples in this research the head of the village chief, Dayun, Secretary of the village, BPD, RW using a sample of the total or the census and RT using technique a sample Random. Data obtained from the questionnaire, interviews and observation, then all data collected then data are grouped according to the type and source of data, the results are presented in the form of tables and in qualitative and quantitative analysis. Based on this analysis techniques researchers assess and conclude that the implementation of authority BPD in the village of Berumbung Baru Dayun Sub-district Siak Regency is located on the category less accomplished. While the obstacles affecting the implementation of the Authority's Berumbung Baru Village BPD Dayun Subdistrict Siak Regency is BPD has a dual role in operate his duties in addition to being a member of the BPD worked as CIVIL SERVANTS and honorary degrees, Less availability of infrastructure and facilities to perform the task and BPD it functions, as well as BPD less know what the duties and authorities for being members of BPD.